A review on high‐temperature thermochemical heat storage: Particle reactors and materials based on solid–gas reactions. Issue 5 (22nd May 2022) - Bellan, Selvan; Kodama, Tatsuya; Gokon, Nobuyuki; Matsubara, Koji
Abstract: In order to produce electricity beyond insolation hours and supply to the electrical grid, thermal energy storage (TES) system plays a major role in CSP (concentrated solar power) plants. Current CSP plants use molten salts as both sensible heat storage media and heat transfer fluid, to operate up to 560°C. To meet the future high operating temperature and efficiency, thermochemical storage (TCS) emerged as an attractive alternatives for next generation CSP plants. In these systems, the solar thermal energy is stored by endothermic reaction and subsequently released when the energy is needed by exothermic reversible reaction. This review compares and summarizes different thermochemical storage systems that are currently being investigated, especially TCS based on metal oxides. Various experimental, numerical, and technological studies on the development of particle reactors and materials for high‐temperature TCS applications are presented. Advantages and disadvantages of different types heat storage systems (sensible, latent, and thermochemical), and particle receivers (stacked, fluidized, and entrained), have been discussed and reported. This article is categorized under: Sustainable Energy > Solar Energy Emerging Technologies > Energy Storage Emerging Technologies > Materials Abstract : Solar thermal Energy storage.